From Doctrine to Action: Islamic Law's Journey towards Social Change - Sumiyati Beddu; Suud Sarim Karimullah; Asbullah Muslim; Nanda Ahmad Basuki; Mu’adil Faizin (Jurnal Wawasan Yuridika, 2024)
This study reveals the journey of Islamic Law from doctrine to social action that brings change. Using a library research method through a comprehensive literature analysis, this study presents the complex challenges of translating Islamic law principles into concrete actions that expand social justice. The findings of this study identify that the gap between idealism and practice is often a major hurdle in implementing Islamic law. Islamic legal theory offers profound guidance on justice, ethics, and morality, emphasizing values such as social justice, general welfare, and protection of individual rights. However, its implementation often faces obstacles that obscure these noble goals. To achieve true social justice, implementing Islamic law must reflect these core values and not just be empty symbolism. It must be applied, embodying justice, benevolence, and the protection of human rights in everyday life.